1986
DOI: 10.1136/sti.62.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of prepuce: case report.

Abstract: SUMMARY A 58 year old man presented with what seemed to be a simple penile lesion, but which on subsequent histological examination proved to be a malignant melanoma. The lesion was excised by circumcision. No further treatment was considered to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…The median age of the SMU patients with glans penis melanoma correlates well with other previous reports 5 , 7 , 10 , 36 and all six lesions arose de novo on the glans as in other series 5 , 7 , 10 , 35 –39 . Unlike other reports, however, no patient stated that the lesion had started as a long‐standing pigmented naevus 5 , 7 , 37 , 39 . Several studies have suggested possible reasons for the delay in diagnosis 5 , 35 , 36 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The median age of the SMU patients with glans penis melanoma correlates well with other previous reports 5 , 7 , 10 , 36 and all six lesions arose de novo on the glans as in other series 5 , 7 , 10 , 35 –39 . Unlike other reports, however, no patient stated that the lesion had started as a long‐standing pigmented naevus 5 , 7 , 37 , 39 . Several studies have suggested possible reasons for the delay in diagnosis 5 , 35 , 36 .…”
Section: Discussionsupporting
confidence: 91%
“…Sometimes the patient is reticent about seeking medical advice through fear of possible malignancy. As the clinical presentation of this rare lesion can be misleading and its benign or malignant nature may not be determined accurately on the basis of clinical findings alone, 7 the lesion may be misdiagnosed as inflammatory or infectious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As anastomoses are common in the lymphatic network of the penis, a lesion may metastasize either contralaterally or bilaterally so bilateral elective lymph node dissection is not recommended in these patients. Nevertheless, some authors suggest that there may be appreciable risk of local recurrence in the penile stump after partial amputation of the penis, so for lesions on the glans, total amputation with block dissection of inguinal nodes is justified [27,29,30,33,34]. The small series reported here would not support this radical approach.…”
Section: Penile Melanomamentioning
confidence: 67%
“…Patients are sometimes reticent about seeking medical advice due to fear of malignancy. Since the clinical presentation of this rare lesion can be misleading and its benign versus malignant nature may not be determined accurately on the basis of clinical findings alone 16 , the lesion can be misdiagnosed as inflammatory or infectious.…”
Section: Case Reportmentioning
confidence: 99%